A facile method for the synthesis of fused perhydropyrano[2, 3-b]pyrans promoted by Yb(OTf)3. Issue 30 (28th March 2018) - Liang, Peng; Pan, Yang; Ma, Xiaofeng; Jiao, Wei; Shao, Huawu
Abstract : A stereospecific three-component domino reaction between glycals, alkylidene malonate and aldehydes catalyzed by Yb(OTf)3 is described. Abstract : A stereospecific three-component domino reaction between glycals, alkylidene malonate and aldehydes catalyzed by Yb(OTf)3 is described. Multi-substituted cis -fused perhydropyrano[2, 3 -b ]pyran derivatives were obtained with high diastereoselectivity.